The Potentialof “Uwi” Plant (Dioscoreasp.) as a Non-Rice Alternative Food Material - Wuryantoro Wuryantoro (Gontor AGROTECH Science Journal, 2020)
“Uwi plant (Dioscorea sp.) as a type of tuber has the potential to support food diversity and food security in the future because it is very tolerant of being planted in all kinds of land including upland. In Indonesia, even in the world, the potential for dry land is very wide and has not been maximally utilized. This study aims to obtain "uwi"-based non-rice alternative food. The organoleptic test was used in this study, using collection materials obtained from the exploration of the ex-Madiun dry land area. The results showed that there was a relationship between the taste and colour of the tuber flesh. White "uwi" is generally preferred, purple colour varies between preferred - dislikes. The medium yellow base colour is not useful until it is not suitable for fresh consumption. The engineering results of synthetic/analogue rice making using "uwi" show that the fresh ingredients give a better colour appearance than the flour treatment. In terms of hardness, fresh ingredients are relatively tougher because the mucus content is still involved in it. In terms of taste, chewiness and texture, it shows that in general, has the same and lower expression than rice and rice. It concluded that the "uwi" plant was very potential to be used for the manufacture of functional rice, especially white and purple coloured yam rice. For other types, it is possible to carry out further research in the direction of bioenergy or pharmacy.